2022
DOI: 10.3899/jrheum.220503
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin A Vasculitis Following COVID-19: A French Multicenter Case Series

Abstract: Objective IgA vasculitis (IgAV) usually occurs following viral respiratory tract infection. The SARS-CoV-2 infection has spread over the world. In this context, we describe a case series of patients who developed IgAV following SARS-CoV-2 infection. Methods This national multicentre retrospective study included patients with IgAV following SARS-CoV-2 infection, from the 1 January 2020 and 1 January 2022. Patients had histologically proven IgAV and RT-PCR proven SARS-CoV-2 infection. The interval time between i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Cases of HS have been reported after Epstein–Barr virus [ 57 , 58 , 59 ], Helicobacter pylori [ 60 ], parainfluenza [ 61 , 62 ], parvovirus B19 [ 63 , 64 , 65 ], Staphylococcus [ 62 ], Streptococcus [ 62 ], and Varicella zoster [ 66 ] infections, cytomegalovirus reactivation [ 67 ], and BCG therapy [ 68 ]. Case reports of HS have been reported following hepatitis A [ 69 ], influenza [ 70 , 71 , 72 , 73 ], MMR [ 74 ], meningitis C [ 75 ], rabies [ 76 ], and SARS-CoV-2 mRNA vaccination [ 77 , 78 , 79 , 80 , 81 , 82 , 83 ]. In contrast to these case reports, a systematic literature review reported no causal association between vaccination and KD or HS [ 84 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cases of HS have been reported after Epstein–Barr virus [ 57 , 58 , 59 ], Helicobacter pylori [ 60 ], parainfluenza [ 61 , 62 ], parvovirus B19 [ 63 , 64 , 65 ], Staphylococcus [ 62 ], Streptococcus [ 62 ], and Varicella zoster [ 66 ] infections, cytomegalovirus reactivation [ 67 ], and BCG therapy [ 68 ]. Case reports of HS have been reported following hepatitis A [ 69 ], influenza [ 70 , 71 , 72 , 73 ], MMR [ 74 ], meningitis C [ 75 ], rabies [ 76 ], and SARS-CoV-2 mRNA vaccination [ 77 , 78 , 79 , 80 , 81 , 82 , 83 ]. In contrast to these case reports, a systematic literature review reported no causal association between vaccination and KD or HS [ 84 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cases of HS have been reported after Epstein-Barr virus [57][58][59], Helicobacter pylori [60], parainfluenza [61,62], parvovirus B19 [63][64][65], Staphylococcus [62], Streptococcus [62], and Varicella zoster [66] infections, cytomegalovirus reactivation [67], and BCG therapy [68]. Case reports of HS have been reported following hepatitis A [69], influenza [70][71][72][73], MMR [74], meningitis C [75], rabies [76], and SARS-CoV-2 mRNA vaccination [77][78][79][80][81][82][83]. In contrast to these case reports, a systematic literature review reported no causal association between vaccination and KD or HS [84].…”
mentioning
confidence: 99%
“…
We would like to discuss the article recently published in The Journal of Rheumatology, entitled "Immunoglobulin A Vasculitis Following COVID-19: A French Multicenter Case Series" by Ramdani et al 1 This case series of individuals who developed IgA vasculitis (IgAV) after contracting SARS-CoV-2 describes the formation of IgAV shortly after coronavirus disease 2019 (COVID-19) infection; however, it was unable to completely rule out a coincidental connection between these 2 events. 1 In most patients, the SARS-CoV-2 infection was paucisymptomatic. The authors advised reverse transcription-PCR tests to identify COVID-19 in patients who had no obvious IgAV triggers.
…”
mentioning
confidence: 99%
“…The authors advised reverse transcription-PCR tests to identify COVID-19 in patients who had no obvious IgAV triggers. 1 Given that comorbidity can be challenging to manage, it is imperative to investigate any potential COVID-19 vaccine issues. 2 Typically, this is not a good alternative if a clinical problem arises following the vaccination.…”
mentioning
confidence: 99%